Application research of virtual fashion shows - Shi, Yaqi (Transactions on Social Science, Education and Humanities Research, 2024)
Virtual fashion has developed from QQ show dressing and Virtual dressing games. With the development of VR and AR technology, the rise of metaverse, virtual Try-On, and virtual fashion shows are also gradually rising. This paper reviews the development of virtual fashion shows, summarizes the form and definition of virtual fashion shows, and analyzes the characteristics and bottlenecks of virtual fashion shows by combining different cases. Starting from the social attribute of virtual fashion shows, this paper puts forward the optimization strategy to promote the sustainable development of virtual fashion shows and enhance its economic benefit.